Therapeutic and Diagnostic Tactics for Bleedings from Esophagogastric Varices - F. G. Nazyrov; R. A. Ibadov; A. V Devyatov; Sh. Kh. Khashimov; N. R. Gizatulina; A. Kh. Babadzhanov (Общая реаниматология, 2010)
Objective: to elaborate therapeutic and diagnostic tactics for bleedings from esophagogastric varices (EGV) in an intensive care unit (ICU). Subjects and methods: The experience in treating 102 patients with profuse bleeding from EGV, admitted to the ICU, Acad. V. Vakhidov Republican Specialized Center of Surgery, in 2000—2008, was summarized. Results. The findings show that just less than 40% of the patients with hepatic cirrhosis are admitted for the clinical manifestations of active bleeding from EGV, the latter being profuse in 17.6%. These indicate that the noticeable admission preponderance of patients with first-degree blood loss and the low proportion of those with critical third-degree blood loss are noteworthy. Retrospective analysis demonstrated that hemostasis was achieved in 97 (95.1%) patients, by applying solely conservative measures using a Blakemore tube (in both variants of its use). After removal of the Blakemore tube, stable hemostasis retained in 88.9% of the patients with bleedings from the veins of the middle third of the esophagus, in 71.8% of cases of those from its lower third and only in 24.1% of the patients with those from the cardiac stomach. Conclusion. According to the results of the study, we propose the therapeutic and diagnostic tactics for patients with profuse bleedings from EGV, which involve the use of a Blakemore tube and a complex of conservative measures with traditional hemostatic therapy, the administration of portal pressure-reducing agents to prevent or treat hepatic failure. Key words: bleeding, esophagogastric varices, hepatic failure, intensive therapy.